THE EFFECT OF GOOD CORPORATE GOVERNANCE ON FIRM VALUE WITH ENVIRONMENTAL COSTS AS MODERATION VARIABLE - Budiman, Jennifer; Christiawan, Yulius Jogi; Angie Alfonso, Natasya (PEOPLE: International Journal of Social Sciences, 2024)
This study aims to examine the effect of good corporate governance on firm value. In addition, this study also examines the role of environmental costs in moderating the effect of good corporate governance on firm value. This research was conducted on go public companies included in the LQ45 index list from 2018 to 2022, with purposive sampling. The data was analyzed using panel data with the weighted least square method. Measurement of good corporate governance uses a score based on the corporate governance perception index, while firm value is measured by the Tobins’Q ratio. Meanwhile, the moderating variable of environmental costs is measured based on Corporate Social Responsibility costs. The results showed that good corporate governance negatively affects firm value. This study did not succeed in proving the moderation of environmental costs on the relationship between good corporate governance and firm value. This research is expected to be the basis for investors in making investment decisions through information about the effect of environmental costs on the relationship between good corporate governance and firm value.